Understanding Hidden Objectives for Developing Teaching Abilities in Prospective Teachers - Rr. Sri Kartikowati; Gimin Gimin (AL-ISHLAH: Jurnal Pendidikan, 2022)
Many lecturers wrote their (formal) learning objectives at the beginning of each session. However, many of them also ignored the existence of hidden objectives, whereas if applied, the hidden objectives will maximize learning outcomes broadly. The hidden objective, that was applied to Micro Teaching courses at the university is discussed. In this paper, we outlined the concept of hidden objectives in developing and nurturing teaching skills for prospective teachers. The article was based on literature analysis relating to the concepts of curriculum, hidden curriculum, and learning objectives. We endeavoured to review the literature, definition, and principles of hidden objectives to develop a better understanding. We concluded that hidden objectives provide a contribution to the Micro Teaching course, and we recommended a model addressed to lecturers at the related departments, to the head of the department where the course was carried out, and to a unit of curriculum development at the Faculty of Education.